Mathematical Simulation of Behavior of Female Breast Consisting Malignant Tumor During Hormonal Changes - Akshara Makrariya; Shishir Kumar Shandilya; Smita Shandilya; Michal Gregus; Ivan Izonin; Rahul Makrariya (IEEE Access, 2022)
The thermal models of human organs for normal, as well as malignant tissues, can be used for generating thermal information for detecting and analyzing tumors. Thermography suffers from the issues of accuracy and specificity. This is due to the non-availability of complete thermal information of human body organs due to benign and malignant disorders. The complete study of thermal patterns in human body organs due to benign and malignant disorders can be useful for generating thermal information for improving the specificity and sensitivity in existing thermographic techniques for the detection of cancer. We have proposed a thermal model of a woman’s breast involving two benign disorders, namely cysts and hormonal changes due to the menstrual cycle. In the proposed model, various critical factors like thermal conductivity and metabolic-heat generation are correlated with blood mass flow while the boundary conditions for acceptance are framed. The model is developed in terms of a boundary-value problem involving the partial equations for a 2-D steady-state case. Thermal patterns within a woman’s breast due to cysts during the presence and absence of various phases of the mensuration cycle are obtained and analyzed. Also, the thermal patterns due to the cyst becoming malignant neoplasm in the Female breast are obtained and analyzed. The substantial differences within thermal patterns in the breast due to malignant tumors and benign disorders like cysts and various phases of the cycle are observed. The thermal information generated from such models is useful to differentiate between benign and malignant disorders by thermography.